Recent Advancements in the Metallurgical Engineering and Electrodeposition - Basheer Al-Naib, Uday; Vikraman, Dhanasekaran; Karuppasamy, K. (IntechOpen, 2020)
Metallurgy is a field of material science and engineering that studies the chemical and physical behavior of metallic elements, intermetallic compounds, and their mixtures, which are called alloys. These metals are widely used in this kind of engineering because they have unique combinations of mechanical properties (strength, toughness, and ductility) as well as special physical characteristics (thermal and electrical conductivity), which cannot be achieved with other materials. In addition to thousands of traditional alloys, many exciting new materials are under development for modern engineering applications. Metallurgical engineering is an area concerned extracting minerals from raw materials and developing, producing, and using mineral materials. It is based on the principles of science and engineering, and can be divided into mining processes, which are concerned with the extraction of metals from their ores to make refined alloys, and physical metallurgy, which includes the fabrication, alloying, heat treatment, joining and welding, corrosion protection, and different testing methods of metals. Conventional metal forming/shaping techniques include casting and forging, which remains an important processing route. Electrodeposition is one of the most used methods for metal and metallic alloy film preparation in many technological processes. Alloy metal coatings offer a wider range of properties than those obtained by a single metal film and can be applied to improve the properties of the substrate/coating system. This book covers a wide range of topics related to recent advancements in metallurgical engineering and electrodeposition such as metallurgy forming, structure, microstructure properties, testing and characterizations, and electrodeposition techniques. It also highlights the progress of metallurgical engineering, the ferrous and non-ferrous materials industries, and the electrodeposition of nanomaterials and composites.